A Highly Conserved Shh Enhancer Coordinates Hypothalamic and Craniofacial Development - Crane-Smith, Zoe; Schoenebeck, Jeffrey; Graham, Katy A.; Devenney, Paul S.; Rose, Lorraine; Ditzell, Mark; Anderson, Eve; Thomson, Joseph I.; Klenin, Natasha; Kurrasch, Deborah M.; Lettice, Laura A.; Hill, Robert E. (Frontiers in Cell and Developmental Biology, 2021)
Enhancers that are conserved deep in evolutionary time regulate characteristics held in common across taxonomic classes. Here, deletion of the highly conserved Shh enhancer SBE2 (Shh brain enhancer 2) markedly reduced Shh expression within the embryonic brain specifically in the rostral diencephalon; however, no abnormal anatomical phenotype was observed due to compensatory low levels of expression mediated by a second enhancer. In contrast, a further reduction of Shh levels, achieved by crossing the SBE2 deletion with the Shh null allele, disrupted brain and craniofacial tissue; thus, linking SBE2 regulated Shh expression to multiple defects and further enabling the study of the effects of differing levels of Shh on embryogenesis. Development of the hypothalamus, derived from the rostral diencephalon, was disrupted along both the anterior-posterior (AP) and the dorsal-ventral (DV) axes. Expression of DV patterning genes and subsequent neuronal population induction were particularly sensitive to Shh expression levels, demonstrating a novel morphogenic context for Shh. The role of SBE2, which is highlighted by DV gene expression, is to step-up expression of Shh above the minimal activity of the second enhancer, ensuring the necessary levels of Shh in a regional-specific manner. We also show that low Shh levels in the diencephalon disrupted neighbouring craniofacial development, including mediolateral patterning of the bones along the cranial floor and viscerocranium. Thus, SBE2 contributes to hypothalamic morphogenesis and ensures there is coordination with the formation of the adjacent midline cranial bones that subsequently protects the neural tissue.